GST and Tax Evasion in India : Evidence from Practitioner Surveys - Bansal, Anuj; Jain, Vranda; Chatterjee, Gourab (Prabandhan: Indian Journal of Management, 2026)
Purpose : This study focused on the effective mechanism of GST as per the views of practicing tax professionals on curbing the circulation of black money and tax evasion in India. Design/Methodology/Approach : For this study, 47 tax professionals (chartered accountants, tax advocates, and company secretaries) were enrolled using purposive expert sampling. The researchers used a quantitative cross-sectional survey design to collect data in January and February 2025. Descriptive statistics, Pearson correlation analysis, and independent variables were used in the data analysis. Findings : The findings indicated that GST achieved only partial success in reducing black money. Real estate remained the most vulnerable sector (M = 3.77). Cash transactions and fake invoicing were the most common evasion methods, and they were correlated with shell companies (r = 0.722). Invoice matching, rated most effective (M = 3.75), showed alignment with e-way bills (r = 0.782). Portal glitches and input tax credit (ITC) errors were key compliance challenges. No significant group differences suggested perceptions reflected objective system performance. Practical Implications : To harness the full anti-evasion potential of GST, targeted digital infrastructure, sector-specific property reforms, and integrated network analysis to detect collusion will be required. Originality/Value : Studies have examined GST’s influence on black money in India. Among the first studies, four experts investigated the effects of GST on black money among tax experts using well-tested, well-recognized statistics.